(untitled) (International Journal of Engineering and Computer Science, 2017)
Automatic detection of disease patterns in medical images can assist radiologists in image analysis. Automated image analysis can be assisted by incorporating into a program information and knowledge that is available to radiologists. In This paper we discuss about detection of various Skin diseases using Region of Interest Extraction using color.